Study of the properties of SBT ceramics doped with different concentrations of Ca. Issue 17 (1st December 2018) - Zhang, Fengqing; Zhao, Xuefeng; Liu, Huiying; Wang, Lingxu; Shen, Peng; Tian, Qingbo; Sun, Huajun; Fan, Suhua
Abstract: This study investigated how Ca doping affects the electrical properties of Sr2 Bi4 Ti5 O18 (SBT) ceramics. Among the samples tested, a sample with a substitution level of 0.15 showed the highest a -axis orientation and the largest lattice distortion. Through XPS analysis, it was found that the formation of oxygen vacancies is suppressed by Ca substitution in SBT. A large remnant polarization (2 Pr ) of 17.7 μC/cm 2 and small coercive field (2 Ec ) of 91 kV/cm was observed for the Ca0.15 Sr1.85 Bi4 Ti5 O18 (CSBT-0.15) ceramic, which indicated that this sample possessed the best ferroelectric properties. As the substitution level increased, the variation of the leakage current density first decreased and then increased, and the sample with the substitution level of 0.15 showed the smallest leakage current density of J = 1.1 × 10 −6 A/cm 2 at 80 kV/cm. For the investigated Cax Sr2-x Bi4 Ti5 O18 (CSBT) ceramic samples, space-charge-limited conduction (SCLC) was determined to be the main conduction mechanism.